ANALISIS KOMPONEN BIOMOTORIK ATLET SEKOLAH SEPAKBOLA (SSB) PSG GADUT KECAMATAN LUBUK KILANGAN KOTA PADANG - Arif Aqli Dasriandi; Didin Tohidin; Ridho Bahtra; Hadi Pery Fajri (Jurnal IKEOR, 2023)
This study aims to determine the Biomotor Ability of PSG Gadut Football School Players (SSB), Lubuk Kilangan District, Padang City which includes speed, agility, strength, flexibility, power and endurance. This research is quantitative descriptive. The method used in this study is a survey method using data collection techniques in the form of tests and measurements. The sample of this study were 17 PSG Gadut Football School (SSB) players. The results of the analysis of the biomotor components with tests and measurements show that the ability of the biomotor components of the largest percentage is as follows: (1) The Speed of the Football School Athlete (SSB) PSG Gadut, Lubuk Kilangan District, Padang City is categorized as Less Once with the largest percentage of 34% , (2) The agility of the PSG Gadut Football School Athlete (SSB), Lubuk Kilangan District, Padang City is categorized as Good with the largest percentage of 34%, (3) The muscle strength of the PSG Gadut Football School Athlete’s (SSB) Lubuk Kilangan District, Padang City is categorized as Less with a percentage the largest is 85%, (4) Flexibility or flexibility Football School Athlete (SSB) PSG Gadut, Lubuk Kilangan District, Padang City is categorized as Less with the largest percentage of 76%, (5) PSG Gadut Football School Athlete Power (SSB) Lubuk Kilangan District, Padang City categorized as Less with the largest per centage of 59%, and (6) Athlete Endurance t PSG Gadut Football School (SSB), Lubuk Kilangan District, Padang City is categorized as Low with the largest percentage of 47%.